2011
DOI: 10.1002/app.34102
|View full text |Cite
|
Sign up to set email alerts
|

New thermoplastic segmented polyurethanes with hard segments derived from 4,4′‐diphenylmethane diisocyanate and methylenebis(1,4‐phenylenemethylenethio)dialcanols

Abstract: New thermoplastic poly(ether-urethane)s and poly(carbonate-urethane)s were synthesized by a onestep melt polymerization from poly(oxytetramethylene) diol (PTMO) and poly(hexane-1,6-diyl carbonate) diol (PHCD) as soft segments, 4,4 0 -diphenylmethane diisocyanate, and 2,20 -[methylenebis(1,4-phenylenemethylenethio)]dihexan-1-ol as unconventional chain extenders. The effects of the kind and amount of the polymer diol and chain extender used on the structure and properties of the polymers were studied. The polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 63 publications
4
34
0
Order By: Relevance
“…This study is a part of an ongoing investigation concerning new TPUs obtained from aliphatic-aromatic sulfur-containing chain extenders, derivatives of, among others, diphenylmethane, diphenylethane, benzophenone, diphenyl ether and diphenyl sulfide [6][7][8][9][10][11][12][13]. On the basis of the studies conducted for selected polymers, it was stated that the introduction of sulfur atoms to the polymer chain improved their adhesive strength [12,[14][15][16] and refractive index [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…This study is a part of an ongoing investigation concerning new TPUs obtained from aliphatic-aromatic sulfur-containing chain extenders, derivatives of, among others, diphenylmethane, diphenylethane, benzophenone, diphenyl ether and diphenyl sulfide [6][7][8][9][10][11][12][13]. On the basis of the studies conducted for selected polymers, it was stated that the introduction of sulfur atoms to the polymer chain improved their adhesive strength [12,[14][15][16] and refractive index [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the aliphatic diisocyanate-based TPUs show no change of colour in the same condition [3]. This paper is a continuation of research on the new TPUs derived from aliphatic-aromatic sulphur-containing chain extenders as well as derivatives of diphenylmethane [5][6][7][8][9][10][11][12][13], diphenylethane [14][15][16], benzophenone [17][18][19], diphenyl ether [20] and diphenyl sulphide [21,22]. Based on the test results, it can be concluded that the introduction of sulphur atoms into the structure of a polymer has increased their adhesive strength [21] and refractive index [11,12].…”
Section: Introductionmentioning
confidence: 72%
“…There appeared also a small peak at approx. 2170 cm -1 , connected with stretching vibrations C-O in carbon monoxide [5]. It indicated that at that temperature the decay of the polyether soft segment took place and its products were aldehydes and aliphatic ethers.…”
Section: Fig 1 Atr-ftir Spectra Of the R-pur And Selected Spursmentioning
confidence: 92%
See 2 more Smart Citations